Preferential binding of hot spot mutant p53 proteins to supercoiled DNA in vitro and in cells - Brázdová, Marie; Navrátilová, Lucie; Tichý, Vlastimil; Němcová, Kateřina; Lexa, Matej; Hrstka, Roman; Pečinka, Petr; Adámik, Matej; Vojtesek, Borivoj; Paleček, Emil; Deppert, Wolfgang; Fojta, Miroslav (PloS one, 2013)
Hot spot mutant p53 (mutp53) proteins exert oncogenic gain-of-function activities. Binding of mutp53 to DNA is assumed to be involved in mutp53-mediated repression or activation of several mutp53 target genes. To investigate the importance of DNA topology on mutp53-DNA recognition in vitro and in cells, we analyzed the interaction of seven hot spot mutp53 proteins with topologically different DNA substrates (supercoiled, linear and relaxed) containing and/or lacking mutp53 binding sites (mutp53BS) using a variety of electrophoresis and immunoprecipitation based techniques. All seven hot spot mutp53 proteins (R175H, G245S, R248W, R249S, R273C, R273H and R282W) were found to have retained the ability of wild-type p53 to preferentially bind circular DNA at native negative superhelix density, while linear or relaxed circular DNA was a poor substrate. The preference of mutp53 proteins for supercoiled DNA (supercoil-selective binding) was further substantiated by competition experiments with linear DNA or relaxed DNA in vitro and ex vivo. Using chromatin immunoprecipitation, the preferential binding of mutp53 to a sc mutp53BS was detected also in cells. Furthermore, we have shown by luciferase reporter assay that the DNA topology influences p53 regulation of BAX and MSP/MST1 promoters. Possible modes of mutp53 binding to topologically constrained DNA substrates and their biological consequences are discussed.
Keywords: Gene Expression Regulation; Protein Binding; mutantní proteiny; protein-serin-threoninkinasy; intracelulární signální peptidy a proteiny; Plasmids; mutace; bcl-2-Associated X Protein; vazebná místa; Cell Line, Tumor; Protein Serine-Threonine Kinases; Intracellular Signaling Peptides and Proteins; promotorové oblasti (genetika); DNA, Superhelical; nádorový supresorový protein p53; protein X asociovaný s bcl-2; Binding Sites; vazba proteinů; substrátová specifita; lidé; Humans; Substrate Specificity; regulace genové exprese; Promoter Regions, Genetic; plazmidy; Mutation; nádorové buněčné linie; superhelikální DNA; Tumor Suppressor Protein p53; Mutant Proteins